Taking Pluralism Seriously : Complex Societies under Scrutiny. - Mathieu, Félix (McGill-Queen's University Press, 2022)
This book offers a theoretical, empirical, and normative analysis of the debates surrounding the accommodation of ethnocultural and societal diversity in contemporary liberal democracies. It invites readers to explore questions about pluralism and accommodation and proposes political reforms to meet the challenges arising from diversity.
Description based upon print version of record.
Keywords: Multiculturalism.; Cultural pluralism.; Multiculturalisme.; Diversité culturelle.; multiculturalism.; POLITICAL SCIENCE / Essays.; Cultural pluralism; Multiculturalism